2022
DOI: 10.1002/sce.21707
|View full text |Cite
|
Sign up to set email alerts
|

Development of the science teaching anxiety scale for preservice elementary teachers: A Rasch analysis

Abstract: Science teaching anxiety is negative emotion that inhibits a teacher's ability to start, proceed, or finish a science teaching task. Despite its detrimental effects on teachers' science teaching quality and practices, there is limited research on science teaching anxiety. To advance research in this area, there is a need for a psychometrically sound instrument assessing teachers' science teaching anxiety. This study presents the development and psychometric properties of the Science Teaching Anxiety Scale (STA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 96 publications
(157 reference statements)
5
7
1
Order By: Relevance
“…For example, Senler (2016) examined the correlation between locus of control, attitudes, teaching anxiety, and self-efficacy. Similarly, Novak et al (2022) created a scale to measure science teaching anxiety amongst preservice teachers. Their findings underscored the importance of…”
Section: Science Teaching Anxietymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Senler (2016) examined the correlation between locus of control, attitudes, teaching anxiety, and self-efficacy. Similarly, Novak et al (2022) created a scale to measure science teaching anxiety amongst preservice teachers. Their findings underscored the importance of…”
Section: Science Teaching Anxietymentioning
confidence: 99%
“…Conversely, anxiety about teaching is negatively correlated with attitudes towards science teaching. A study by Novak et al (2022) discovered a noteworthy association between anxiety related to teaching science, interest in science, and self-efficacy in teaching. The study revealed a negative association between anxiety related to teaching and both self-efficacy and interest in teaching science.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…These scales consist of the SAQ from 44 items, SAS from 28 items and ASST from 21 items. Scales were developed to measure science anxiety at high school (Mehar & Singh, 2018) and university level (Novak et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding teachers’ occupational anxiety, studies had found that the types were mainly related to subject anxiety, such as mathematics ( Peker and Ertekin, 2011 ; Ganley et al, 2019 ; Bosica, 2022 ), English ( Liu and Wu, 2021 ), and science ( Novak et al, 2022 ). For example, Bosica (2022) investigated mathematics teaching anxiety and mathematics anxiety among in-service elementary school teachers in Ontario.…”
Section: Introductionmentioning
confidence: 99%